2007
DOI: 10.1002/ardp.200600145
|View full text |Cite
|
Sign up to set email alerts
|

Aminocarbonyloxymethyl Ester Prodrugs of Flufenamic Acid and Diclofenac: Suppressing the Rearrangement Pathway in Aqueous Media

Abstract: Aminocarbonyloxymethyl ester prodrugs are known to undergo rearrangement in aqueous solutions to form the corresponding N-acylamine side product via an O-->N intramolecular acyl transfer from the carbamate conjugate base. Novel aminocarbonyloxymethyl esters of diclofenac and flufenamic acid containing amino acid amide carriers were synthesized and evaluated as potential prodrugs displaying less ability to undergo rearrangement. These compounds were prepared in reasonable yield by a four-step synthetic method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Notably, various prodrugs derived from NSAIDs containing carboxylic group were prepared in which the carboxylic group was masked, but it has been shown that a major requisite for these prodrugs is that they must be readily hydrolyzed, enzymatically or chemically, to quantitatively release the parent NSAID drug. 54 DCF Ligands Released From cis-[Pt(DCF) 2 (NH 3 ) 2 ] (3) Alter Cell Cycle Profile. To further characterize the cytotoxic effect of 3, an analysis of the cell cycle perturbations was performed in HeLa cells exposed to 3, or to the reference compound cisplatin and free DCF.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…Notably, various prodrugs derived from NSAIDs containing carboxylic group were prepared in which the carboxylic group was masked, but it has been shown that a major requisite for these prodrugs is that they must be readily hydrolyzed, enzymatically or chemically, to quantitatively release the parent NSAID drug. 54 DCF Ligands Released From cis-[Pt(DCF) 2 (NH 3 ) 2 ] (3) Alter Cell Cycle Profile. To further characterize the cytotoxic effect of 3, an analysis of the cell cycle perturbations was performed in HeLa cells exposed to 3, or to the reference compound cisplatin and free DCF.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…Presumably, converting diclofenac to some appropriate prodrugs within the optimal partition coefficient range could achieve higher transdermal penetration. Diclofenac prodrugs have been widely explored, but mostly for the purposes of reducing gastric irritation after oral administration or improving anti-inflammatory efficacy[12-14], with the exception of two studies on diclofenac prodrugs for enhancing transdermal delivery [15, 16]. In those two studies, diclofenac prodrugs were formed by converting diclofenac to diclofenac esters (formed ester with ethylene glycol in one study, and formed esters with different chain length of polyoxyethylene glycols in the other study), and better transdermal permeation was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of latentiation as a molecular modification strategy provides NSAID produgs with improved safety profiles [ 3 , 4 ]. The prodrug approach afforded compounds with better anti-inflammatory activity, differentiated pharmacokinetic profiles and reduced gastric ulcerogenic activity [ 5 , 6 , 7 , 8 , 9 ]. Using the prodrug approach, one strategy that could be useful is to temporarily mask the carboxylic acid function of the NSAIDs so the prodrug hydrolyzes in vivo to release the active parent NSAID [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%